Augmented Reality (AR) Solar System Learning Application - Koh, Ka Haw; Ezak Fadzrin Ahmad Shaubari (Applied Information Technology And Computer Science, 2021)
Using conventional learning materials to learn Solar System topic in Year 4 primary school is dry on concept learning, interaction, motivation, and required imagination, so the project aims to design and develop a Solar System mobile learning application by using Augmented Reality (AR) as the medium and to test the bugs, discrepancies of the proposed application, and feedback from the Year 4 primary school students. The proposed application will be designed for the AR solar system learning application with an interactive AR module, mini quiz (2D), and mini learning game (2D) module to increase the interaction and motivation with the students. The development of augmented reality (AR) solar system application is based on the Multimedia Mobile Content Development (MMCD) methodology which contains 5 main stages which are application idea creation stages, structure analysis stages, process design stages, main function development stages, and testing stages. From the user testing results, there is an average of eighty-four per cent of respondents gave positive feedback to the Solar System World. Provide additional languages, develop the reward system and develop the health-improving system will be the future work to improve the current limitations of the Solar System World.